Rubinstein–Taybi syndrome with humoral and cellular defects: a case report. Issue 4 (1st October 2000) - Villella, Anthony; Bialostocky, Dalia; Lori, Eli; Meyerson, Howard; Hostoffer, Robert W
Abstract : THE FIRST ASSOCIATION OF RUBINSTIEN: Taybi syndrome with immunodeficiency and the successful prevention of infection with intravenous IgG is reported in a 4 year old boy. This case suggests that immunodeficiency maybe a prominent feature of this syndrome and may predispose these patients to recurrent infections.